'I Sometimes Catch Myself Looking Angry or Tired …': The Impact of Mediating by Zoom. Issue 5 (29th April 2021) - Golann, Dwight
Abstract : To learn how mediating over the Internet is changing mediation, I asked 20 leading mediators from the U.S., Canada, and Britain, who together had conducted more than 1, 000 Zoom mediations, what was different about mediating by video. Here is what they told me.